Análisis de la meteorización química y proveniencia en lateritas subtropicales de Misiones - Campodonico, Verena Agustina (2019)
Subtropical laterites in Misiones province cover the Jurassic-Cretaceous Serra Geral basalts. Two hypotheses have been proposed to explain the origin of these laterites. The autochthonous theory states that these deposits result from chemical weathering of the underlying tholeiitic basalts. However, during the last decade, an allochthonous “tropical loess” model was proposed. A lateritic profile (~2 m thick, 26°9'58"S - 54°35'3"W) was analyzed in order to constrain the nature of weathering processes and the provenance of the lateritic layer. Different alteration indices showed the extreme leaching of the basaltic bedrock. The index of lateritization (IOL = 35-50) and the accompanying SAF ternary plot (SiO2-Al2O3-Fe2O3), indicate an increasing weathering trend towards the profiles' top, reflecting the modest loss of SiO2 (relative to Al2O3 and Fe2O3) during kaolinitization. The geochemical approach used in this work clearly relates the analyzed laterites to the underlying tholeiitic basalts, supporting the autochthonous origin theory.